2013
DOI: 10.1016/j.jpainsymman.2012.10.064
|View full text |Cite
|
Sign up to set email alerts
|

Job Satisfaction, Intent to Leave, and Work Improvements as Perceived By Hospice and Palliative Nursing Assistants (TH330-C)

Abstract: Method. We included all patients seen within the community-based Carolinas Palliative Care Consortium from 6/2008 through 12/2011. Patients were stratified into two cohorts: one where QOL remained the same or decreased; the other where QOL increased. Demographics, palliative performance score (PPS) and estimated life expectancy, and PC processes were characterized and compared. Univariate and multivariate logistic regression identified associations between PC interventions and increase in QOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…간호사 측면에 서는 간호사의 업무 참여를 고취시키고 [8], 직무만족을 높인다 [9]. 또한, 간호관리자, 신규간호사, 호스피스간호 사 등 다양한 분야의 업무에 종사하는 간호사를 대상으 로 한 선행연구 결과, 간호사 본인이 소속된 의료기관에 대한 간호근무환경을 좋게 인식할수록 이직의도를 감소 시키는 긍정적인 영향이 있는 것으로 드러났다 [10,11,12,13]. 이에 간호근무환경은 간호사가 조직에 오 래 머물도록 하는데 중요한 선행요인으로 제시되었다 [14,15,16] …”
Section: 서론unclassified
“…간호사 측면에 서는 간호사의 업무 참여를 고취시키고 [8], 직무만족을 높인다 [9]. 또한, 간호관리자, 신규간호사, 호스피스간호 사 등 다양한 분야의 업무에 종사하는 간호사를 대상으 로 한 선행연구 결과, 간호사 본인이 소속된 의료기관에 대한 간호근무환경을 좋게 인식할수록 이직의도를 감소 시키는 긍정적인 영향이 있는 것으로 드러났다 [10,11,12,13]. 이에 간호근무환경은 간호사가 조직에 오 래 머물도록 하는데 중요한 선행요인으로 제시되었다 [14,15,16] …”
Section: 서론unclassified
“…In other words, favorable nursing work environments have resulted in nurses’ increased participation and improved job satisfaction [ 13 , 14 ]. Previous studies of nurses in various fields, such as nursing managers, new nurses, and hospice nurses, have shown that the more positively nurses perceive their nursing work environment in healthcare institutions, the lower their turnover intention [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%